2004
DOI: 10.1016/j.accreview.2004.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygen level-dependent magnetic resonance imaging in patients with stress-induced angina

Abstract: Background-Blood oxygen level-dependent (BOLD) MRI reflects tissue oxygenation and may be useful for the detection of myocardial ischemia in patients with suspected coronary artery disease. Methods and Results-We studied 25 patients with stress-induced angina using a T 2 *-sensitive echo planar imaging sequence before and during adenosine in a single-slice approach. BOLD-MRI results were compared with quantitative angiography and adenosine thallium single-photon emission computed tomography (SPECT). Although i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 7 publications
4
35
2
Order By: Relevance
“…These results confirmed previous study data reporting a close correlation between BOLD signal intensity changes and the degree of coronary stenosis ( Figure 8). 44 Overall, an improved diagnostic value for the detection of significant coronary stenosis was seen (Table 1). In addition, myocardial segments consisting predominantly of scar tissue as defined by LGE imaging exhibited constant BOLD signal intensities at rest and during vasodilator stress as a result from the scarcely capillarized scarred myocardium without any vasodilatory capacity.…”
Section: Clinical Application Of Bold Cmr Imaging At 30 Teslamentioning
confidence: 89%
See 2 more Smart Citations
“…These results confirmed previous study data reporting a close correlation between BOLD signal intensity changes and the degree of coronary stenosis ( Figure 8). 44 Overall, an improved diagnostic value for the detection of significant coronary stenosis was seen (Table 1). In addition, myocardial segments consisting predominantly of scar tissue as defined by LGE imaging exhibited constant BOLD signal intensities at rest and during vasodilator stress as a result from the scarcely capillarized scarred myocardium without any vasodilatory capacity.…”
Section: Clinical Application Of Bold Cmr Imaging At 30 Teslamentioning
confidence: 89%
“…Consequently, in patients with chest pain syndromes BOLD CMR imaging offered a good sensitivity in comparison to quantitative coronary angiography but resulted in a low specificity. 44 Considering only patients with angiographically diagnosed triple-vessel disease a stress-induced decrease of the BOLD signal was observed in 81% of segments though a global change affecting all myocardial segments was expected. 47 It was speculated that the stress-induced increase in myocardial oxygenation in the remaining myocardial segments may be attributed to a still existing residual vasodilator capacity and, thus, the morphological stenoses did not result in an overall functional relevance.…”
Section: Clinical Studies Using Bold Cmr Imagingmentioning
confidence: 92%
See 1 more Smart Citation
“…A T 2 increase would also result in increased T 2 * as seen from Equation (1). Further to this, reduced myocardial perfusion and ischemia are common in HCM [109], effectively reducing the tissue blood volume fraction resulting in a T 2 * increase as suggested by Equation (5). These conditions are also associated with a higher risk for a poor outcome in HCM patients [110].…”
Section: Myocardial T 2 * Mapping In Patients With Cardiovascular Dismentioning
confidence: 96%
“…By exploiting the blood oxygenation level-dependent (BOLD) effect [3], T 2 * sensitized CMR has been proposed as a means of assessing myocardial tissue oxygenation and perfusion. T 2 * mapping has been shown to be capable of detecting myocardial ischemia caused by coronary artery stenosis [4], to reveal myocardial perfusion deficits under pharmacological stress [5][6][7][8][9][10], to study endothelial function [11] or to assess breathing maneuver-dependent oxygenation changes in the myocardium [12][13][14][15]. Preclinical studies have also demonstrated the potential of T 2 * mapping to detect structural changes in the infarcted heart muscle and even to distinguish between focal and diffuse fibrosis [16][17][18].…”
Section: T 2 * Sensitized Cardiovascular Magnetic Resonancementioning
confidence: 99%